2020
DOI: 10.3390/ijerph17207389
|View full text |Cite
|
Sign up to set email alerts
|

Is Consultation-Liaison Psychiatry ‘Getting Old’? How Psychiatry Referrals in the General Hospital Have Changed over 20 Years

Abstract: There is an ever-growing awareness of the health-related special needs of older patients, and Consultation-Liaison Psychiatry Services (CLPS) are significantly involved in providing such age-friendly hospital care. CLPS perform psychiatric assessment for hospitalized patients with suspected medical-psychiatric comorbidity and support ward teams in a bio-psycho-social oriented care management. Changes in features of the population referred to a CLPS over a 20-year course were analysed and discussed, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The high rates of referrals for delirium are in line with previous evidence that indicates an overall aging of the inpatient population in GHs and reveal a high incidence of delirium in the inpatient setting [ 35 , 36 ], a common reason for psychiatric referral [ 22 , 24 , 37 ]. The fair diagnostic accuracy found for delirium (which rose to moderate when the presentation was associated with agitation) indicates a remarkable and well-known risk that GH doctors may miss a delirium diagnosis [ 36 , 38 ], particularly in case of hypo-active delirium [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…The high rates of referrals for delirium are in line with previous evidence that indicates an overall aging of the inpatient population in GHs and reveal a high incidence of delirium in the inpatient setting [ 35 , 36 ], a common reason for psychiatric referral [ 22 , 24 , 37 ]. The fair diagnostic accuracy found for delirium (which rose to moderate when the presentation was associated with agitation) indicates a remarkable and well-known risk that GH doctors may miss a delirium diagnosis [ 36 , 38 ], particularly in case of hypo-active delirium [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…Prolonged hospital stays are a major challenge for health systems and present high associated economic costs. Research has confirmed how effective CLP unit clinical actions may help improve outcome indicators of health care, i.e., quality of life and disability of patients, length of hospital stay, and health costs [ 31 ]. A rapid and effective participation of the liaison psychiatrist is therefore relevant and is aligned with the proactive model of care of a CLP unit; this participation also focuses on early psychiatric care in medical and surgical settings, which has been shown to decrease LOS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this Feature Paper Special Issue entitled “ Age-Friendly Cities and Communities: State of the Art and Future Perspectives ”, a total of 29 papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] were recently published on different topics related to this subject matter. Of the published papers, seven papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] related to age-friendly neighbourhoods, cities, communities and societies, three papers [ 29 , 30 , 31 ] explored innovative approaches to housing, two papers [ 32 , 33 ] concentrated on age-friendly transportation, four papers [ 34 , 35 , 36 , 37 ] focused on innovative practices in the domain of cure and/or care for older citizens, four papers [ 38 , 39 , 40 , 41 ] related to respect and social inclusion, and nine papers [ 42 , …”
mentioning
confidence: 99%
“…The study by Ferrari et al [ 34 ] from Italy focused on age-friendly hospital care. Consultation–Liaison Psychiatry Services (CLPS) are significantly involved in providing age-friendly hospital care.…”
mentioning
confidence: 99%
See 1 more Smart Citation